2010
DOI: 10.1007/s00436-010-2058-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of the crude extracts, fractions, and osthole from Radix angelicae pubescentis against Dactylogyrus intermedius in goldfish (Carassius auratus) in vivo

Abstract: A bioassay-guided fractionation was performed to evaluate the anthelmintic activity of the crude extract fractions and osthole from Radix angelicae pubescentis against Dactylogyrus intermedius in goldfish (Carassius auratus) in vivo. Among four extracts (petroleum ether, ethyl acetate, acetone, and ethanol), only ethanol extract exhibited the best anthelmintic efficacy with 100% mortality of Dactylogyrus and no death of fish at the optimal anthelminthic concentration of 120 mg/L. Therefore, ethanol extract was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…The efficacy of these agents against D. intermedius has been shown to be variable. Wang et al (2010a) found that the efficacy of steroidal saponins from Dioscorea zingiberensis was up to 90% and Wang et al (2011) found that osthol extract from Radix angelicae pubescentis had efficacy of 100%. On the other hand, Huang et al (2013) reported that ethyl acetate extract from Lysima chiachristinae presented 50% efficacy against D. intermedius.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The efficacy of these agents against D. intermedius has been shown to be variable. Wang et al (2010a) found that the efficacy of steroidal saponins from Dioscorea zingiberensis was up to 90% and Wang et al (2011) found that osthol extract from Radix angelicae pubescentis had efficacy of 100%. On the other hand, Huang et al (2013) reported that ethyl acetate extract from Lysima chiachristinae presented 50% efficacy against D. intermedius.…”
Section: Discussionmentioning
confidence: 98%
“…The anthelmintic activity of oils or plant extracts has been evaluated mainly against monogenean parasites of goldfish (Carassius auratus) (Steverding et al, 2005;Wang et al, 2009;Wang et al, 2010aWang et al, , 2010bWang et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment with pure artemisinin crystals showed faster effects on the parasites compared with the plant extracts (Ekanem & Brisibe 2010). Bath treatments of Dactylogyrus intermedius ‐infected goldfish in crude ethanol extract of the Chinese herb Radix angelicae pubescentis were found to be 100% effective against D. intermedius at an optimal concentration of 120 mg L −1 , whereas osthole, the principal anthelmintic bioactive compound isolated from the plant, exhibited optimal activity with 100% mortality of the parasite at 1.6 mg L −1 (Wang et al. 2011).…”
Section: Differential Uses Of Phytochemicals In Finfish Culturementioning
confidence: 99%
“…RAB extracts using different solvents have quite different effects on treating ring worm. ARAB exhibited the best anthelmintic efficacy with 100% mortality of dactylogyrus and no death of the fish at the optimal anthelminthic concentration of 120 mg/L (Wang et al, 2011c;Xie et al, 2016). Osthole (17) can reach the 100% parasiticidal rate when the concentration was 1.6 mg/L, with no toxicity to fish at a dose up to 6.2 mg/L.…”
Section: Deworming Activitymentioning
confidence: 99%